2016
DOI: 10.1074/jbc.c116.741397
|View full text |Cite
|
Sign up to set email alerts
|

Starch Binding Domain-containing Protein 1 Plays a Dominant Role in Glycogen Transport to Lysosomes in Liver

Abstract: A small portion of cellular glycogen is transported to and degraded in lysosomes by acid ␣-glucosidase (GAA) in mammals, but it is unclear why and how glycogen is transported to the lysosomes. Stbd1 has recently been proposed to participate in glycogen trafficking to lysosomes. However, our previous study demonstrated that knockdown of Stbd1 in GAA knockout mice did not alter lysosomal glycogen storage in skeletal muscles. To further determine whether Stbd1 participates in glycogen transport to lysosomes, we g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 27 publications
0
39
2
Order By: Relevance
“…(29) In this respect, a recent study indeed indicates that lysosomal glycogen breakdown and autophagosome formation are differentially regulated. (30) Our data appear contradictory to findings reported by Rother and Schwenk, who concluded that increased glycogen cycling cannot account for residual EGP in GSD I. Using enteral infusion of 13 C-glucose and galactose, these investigators found that increased glucose infusion suppressed EGP in GSD I patients but simultaneously enhanced UDP-glucose turnover.…”
Section: Discussioncontrasting
confidence: 99%
“…(29) In this respect, a recent study indeed indicates that lysosomal glycogen breakdown and autophagosome formation are differentially regulated. (30) Our data appear contradictory to findings reported by Rother and Schwenk, who concluded that increased glycogen cycling cannot account for residual EGP in GSD I. Using enteral infusion of 13 C-glucose and galactose, these investigators found that increased glucose infusion suppressed EGP in GSD I patients but simultaneously enhanced UDP-glucose turnover.…”
Section: Discussioncontrasting
confidence: 99%
“…STBD1 is a N-terminally membrane anchored [38] glycogen-binding [25,39] protein that localizes glycogen to perinuclear sites/ER, late endosomes and lysosomes and is most abundantly expressed in muscle and liver [25]. The lower expression of STBD1 we observed in CCF together with its involvement in the lysosomal glycogen degradation pathway [27] suggests that this reduction of STBD1expression could be an additional factor contributing to glycogen accumulation in CCF. However, a significant glycogen accumulation in livers of Stbd1-KO mice was not observed.…”
Section: Stbd1mentioning
confidence: 68%
“…An Atg8 family interacting motif (AIM) and interaction with GABARAPL1 implicated STBD1 to be involved in autophagic glycogen degradation, so called glycophagy [26]. In a mouse model of Pompe disease, deletion of STBD1 suppressed lysosomal glycogen accumulation, suggesting STDB1 to be involved in transfer of glycogen from the cytoplasm to lysosomes [27]. The reduced expression of STBD1 in CCF could be responsible for the hepatocellular glycogen accumulation.…”
Section: Loss Of Stbd1 In Mice Does Not Cause Glycogen Accumulation Imentioning
confidence: 99%
See 1 more Smart Citation
“…SBDs were originally recognized as a module found typically in microbial amylolytic and related enzymes. It is worth mentioning that various SBDs and GBDs have also been identified in other plant and animal enzymes and proteins, such as plant starch synthase III, glucan‐water dikinases, starch‐excess protein‐4, animal laforin, genethonin‐1, as well as the β‐subunit of AMP‐activated protein kinase and its homologues in plants, and even in lytic polysaccharide monooxygenases from fungi . Nevertheless, as for the microbial SBDs, generally the non‐microbial SBDs or GBDs are always involved in metabolism of starch and/or glycogen, or other α‐glucans …”
Section: Introductionmentioning
confidence: 99%